Pulse-width modulation pre-emphasis applied in a wireline transmitter, achieving 33 dB loss compensation at 5-Gb - Schrader, J.-R (IEEE Journal of solid state circuits)
A transmitter pre-emphasis technique for copper cable equalization is presented that is based on pulse-width modulation (PWM). This technique is an alternative to the usual 2-tap symbol-spaced FIR (SSF) pre-emphasis. The technique uses timing resolution instead of amplitude resolution to adjust the filter transfer function, and therefore fits well with future high-speed low-voltage CMOS processes. Spectral analysis and time domain simulations illustrate that PWM pre-emphasis offers more relative high frequency boost than 2-tap SSF. Only one coefficient needs to be set to fit the equalizer transfer function to the channel, which makes convergence of an algorithm for automatic adaptation straightforward. A proof-of-concept 0.13-μm CMOS transmitter achieves in excess of 5 Gb/s (2-PAM) over 25 m of standard RG-58U low-end coaxial copper cable with 33 dB of channel loss at the Nyquist frequency (2.5 GHz). Measured BER at this speed and channel loss is <10-12.